Antigen Epitope Developed Based on Acinetobacter baumannii MacB Protein Can Provide Partial Immune Protection in Mice. (20th October 2020) - Song, Xiaojie; Zhao, Guanghui; Ding, Meiling
Abstract : Acinetobacter baumannii ( A. baumannii ) is an important opportunistic pathogen widely present in medical environment. Given its complex drug resistance, A. baumannii poses a serious threat to the safety of critically ill patients. Given the limited alternative antibiotics, nonantibiotic-based functional anti- A. baumannii infection proteins must be developed. In this study, we firstly used a series of biological software to predict potential epitopes in the MacB protein sequence and verified them by antibody recognition and lymphocyte proliferation tests. We finally screened out B cell epitope 2, CD8 + T cell epitope 7, and CD4 + T cell epitope 11 and connected them to construct a recombinant antigen epitope (RAE). The determination of IgG in the serum of immunised mice and cytokines in the supernatant of lymphocytes showed that the constructed epitope induced an immune response mediated by Th-1 cells. Finally, the challenge experiment of A. baumannii infection in mice confirmed that the epitope developed based on MacB, especially RAE, provided incomplete immune protection for mice.